If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (H + 6)(h + -2) * h = 672 Reorder the terms: (6 + H)(h + -2) * h = 672 Reorder the terms: (6 + H)(-2 + h) * h = 672 Reorder the terms for easier multiplication: h(6 + H)(-2 + h) = 672 Multiply (6 + H) * (-2 + h) h(6(-2 + h) + H(-2 + h)) = 672 h((-2 * 6 + h * 6) + H(-2 + h)) = 672 h((-12 + 6h) + H(-2 + h)) = 672 h(-12 + 6h + (-2 * H + h * H)) = 672 h(-12 + 6h + (-2H + hH)) = 672 Reorder the terms: h(-12 + -2H + 6h + hH) = 672 h(-12 + -2H + 6h + hH) = 672 (-12 * h + -2H * h + 6h * h + hH * h) = 672 (-12h + -2hH + 6h2 + h2H) = 672 Solving -12h + -2hH + 6h2 + h2H = 672 Solving for variable 'h'. Reorder the terms: -672 + -12h + -2hH + 6h2 + h2H = 672 + -672 Combine like terms: 672 + -672 = 0 -672 + -12h + -2hH + 6h2 + h2H = 0 The solution to this equation could not be determined.
| 0.6x+1.18=0.8x+6.18 | | -28=3x | | (4.5)18x=126 | | 132/11=n | | 0.25w+0.17f=80000 | | (4.5)(18)x=126 | | 11x+12y-10=0 | | 2ln(x+7)=2.7 | | 7x+5+5x= | | -7=1+2 | | 4.5*18x=126 | | -7x-8x=-15 | | t/2-1=0 | | b^3*b^2=0 | | 4/7t-1/14t=t-9/2 | | (W+40)w=6000 | | .6612+4x+4x^2=0 | | 3+3s-(4s+1)-(2s+6)= | | -8y-1=-7y-6 | | 6x-12=16x-8 | | 2/3k=28.4/9 | | 2r-3s=-8 | | 2c+4=20 | | -35x^2+2x-1=0 | | (-3a-7)-(-a+9)= | | 7x-2yforx-5andy=3 | | (8y^5)1/3 | | 8-5=4p-1 | | 3(y-5)=2y+2 | | 3x-y=22x-y=3byelimination | | cos(3x)+cos(5x)=0 | | 60x^2y-70x^4zw= |